Parent's Knowledge and Anxiety Levels in Covid-19 Vaccination Program in Children Aged 6-11 Years in Lamongan - Ubudiyah, Masunatul; Sholikhah, Siti; Saifudin, Moh.; Rahmawati, Dita Elma Mei Fita Nur; Aris, Arifal (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: COVID-19 prevention is currently a major concern for WHO, especially administering the COVID-19 vaccine. However, there are still several problems underlying the achievements of the vaccine administration program in Indonesia, especially the administration of the COVID-19 vaccine to children aged 6-11 years. This study aimed to the relationship between parental knowledge and anxiety levels in implementing the COVID-19 vaccination program for children aged 6-11 years in Lamongan, Indonesia. Method: This study used a cross-sectional design involving a total of 195 respondents. The research was conducted in Lamongan by measuring the level of knowledge and anxiety level of parents in administering the COVID-19 vaccine. The researcher used an instrument of a knowledge level questionnaire and the Hamilton Anxiety Rating Scale (HARS) which had been tested for validity and reliability, Data were analyzed using pearson correlation test with SPSS. Results: The results showed that 42.6% had sufficient knowledge and only a small proportion of 24.6% had good knowledge. The level of anxiety shows that 49.7% is in the level of severe anxiety and 4.6% is in the level of mild anxiety. Parents with low levels of knowledge also have an impact on severe levels of anxiety. The results of the Pearson correlation test analysis show of sig 2-tailed = 0.002, which means that between the variable parental knowledge and the variable level of anxiety has a significant relationship with the value of the correlation coefficient = 0.223. Conclusions: There is a relationship between the level of knowledge and the anxiety level of parents in administering the COVID-19 vaccine to children aged 6-11 years. Health education related about the benefits and impacts of giving the COVID-19 vaccine needs to be conveyed clearly to the public.